Competencias pedagógicas para la formación jurídica por competencias - Goyes Moreno, Isabel (2013)
This paper aims to stimulate a necessary discussion on the subject of teaching skills that law's professors require to form at competences, this mean, to form for being, knowing and doing, as today social, economics, and disciplinarians needs in a globalized world, as well as, national and institutional regulations. The thesis that arises is that as long as there are no changes in classroom practices that are commonly used by teachers and students, curriculum theoretical transformations will be a purely formal change without possibility of affecting neither the work of the academy work nor training processes or student learning. The challenge facing university teachers is the urgency to reflect on their traditional know-how, in order to establish if it responds to the needs of the present.